Proceedings of the Ninth International Conference on Future Energy Systems 2018
DOI: 10.1145/3208903.3213522
|View full text |Cite
|
Sign up to set email alerts
|

A demonstration of monitoring and measuring data centers for energy efficiency using opensource tools

Abstract: Data centers are complex systems that require sophisticated operational management approaches to provide the availability of digital services against the backdrop of cost and energy eiciency. To achieve this, data center telemetry data is required since, as is commonly said it is not possible to manage what cannot be measured. This paper details how it is possible to construct the key data center infrastructure management (DCIM) elements of monitoring and measuring by a combination of available opensource soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…The SICS ICE is a data centre envisioned for different research projects and established by SICS Swedish ICT in partnership with Luleå University of Technology and it is located in Luleå, Sweden [26]. In this study, we focus on the simulation of Module 1 of the SICS ICE facility [40] which is demonstrated in FIGURE 1.…”
Section: A Modelling the Testbedmentioning
confidence: 99%
See 1 more Smart Citation
“…The SICS ICE is a data centre envisioned for different research projects and established by SICS Swedish ICT in partnership with Luleå University of Technology and it is located in Luleå, Sweden [26]. In this study, we focus on the simulation of Module 1 of the SICS ICE facility [40] which is demonstrated in FIGURE 1.…”
Section: A Modelling the Testbedmentioning
confidence: 99%
“…As shown in FIGURE 1 (a), the module is a 5 m×6.5 m room, consists of 10 server racks (Rack 1-10), and 4 cooling devices (SEE Cooler 1-4). The racks assemble the computational capabilities of Module 1, each rack contains 18 servers each of them equipped with four 4TB 7200rpm hard drives, 256GB RAM, two Intel Xeon E5-2620 v3 2.4GHz CPUs and six Delta PFR 60 × 60 local fans [40]. In terms of modelling of thermal behaviour and energy consumption, we use only models of CPUs and local fans as components of server model.…”
Section: A Modelling the Testbedmentioning
confidence: 99%
“…Traditionally, the data center industry has addressed inefficiencies primarily through hardware innovation -more efficient CPUs, better cooling solutions, improved power distribution systems, etc. However, there is huge scope to offer better efficiencies through software-only solutionsexamples include more powerful monitoring and analysis of data center systems [16], predictive capacity planning [17], CFD-based floor layout tools [18], and intelligent scheduling mechanisms [19]. One common factor that is necessary when developing real-world solutions in this space is the need for multi-disciplinary, holistic thinking -it is not enough to view such a system in isolation; instead solutions need to consider the interactions between the physical systems, software systems, business processes, and user behaviors.…”
Section: Takedownmentioning
confidence: 99%
“…Detailed flow analysis of hard floor and raised floor setups in the SICS ICE data center in Luleå, Sweden, has previously been performed with numerical simulations [7,15,16] and measurements [17,18]. The influence of a turbulence model on the fluid flow in a hard floor server room was investigated by Wibron et al [15], recommending the Reynolds stress model (RSM) for modeling the flow on a server room scale.…”
Section: Introductionmentioning
confidence: 99%